101 The Barrow Randomized OR Traffic (BRITE) Trial: The Effect of OR Traffic on Infection Rates. (August 2015) - Bohl, Michael; Clark, Justin C.; Oppenlander, Mark E.; Meeusen, Andrew J.; Budde, Alex; Porter, Randall W.; Spetzler, Robert F.
Abstract : INTRODUCTION: Surgical site infections (SSI) contribute significantly to patient morbidity and mortality and greatly increase health care costs. It has been postulated that increased traffic through operating rooms (ORs) during procedures increases SSI rates. METHODS: We conducted a 2-phase clinical trial to determine whether increased OR traffic was associated with increased SSI rates. Infrared personnel counters were installed on all doors accessing the 11 neurosurgical ORs at our institution. Phase 1 was a prospective observational study in which all traffic in and out of an OR during a case was counted for a period of 21 weeks. Phase 2 was a randomized, single-blinded trial composed of 2 study arms: patients assigned to ORs where traffic was restricted, and those assigned to regular traffic ORs. This phase lasted 12 weeks. All patients were followed for 8 weeks following their procedure to capture the incidence of SSI. RESULTS: One thousand nine hundred forty-four cases were performed during the observational phase. Thirty-four patients met the CDC criteria for SSI (overall SSI rate = 1.75%). Predictors of SSI included case type and case length. There was no correlation between traffic rate and SSI rate ( P = .782). Phase 2 included 1116 cases. The low-traffic (LT) and regular traffic (RT) arms were not significantly different in size, case type, case length, nor any other factors analyzed as possible confounders. Twenty-six patients met CDC criteria for SSI. Numerous statistical analyses showed no effect of the LT protocol ( P = .059 trend toward higher SSI rate in the LT arm) nor actual traffic rate ( P = .751) on SSI risk. CONCLUSION: In conclusion, OR traffic can be significantly reduced by using a LT protocol like that used in this study. However, significantly reducing OR traffic does not meaningfully reduce the risk of SSI.